ALOKASI BIAYA OVERHEAD PABRIK BERDASARKAN ACTIVITY BASED COSTING DALAM MENENTUKAN HARGA POKOK PRODUKSI PADA ANDRA BAKERY MEDAN - Lidiani, Helde (Jurnal Ilmiah Akuntansi (JIMAT), 2022)
This study aims to determine and analyze how the allocation of factory overhead costs based on activity based costing in determining the cost of production at Andra Bakery Medan. The population in this study is data regarding costs related to the Cost of Production, namely direct processing data and factory overhead costs at Andra Bakery Medan from the year it was founded until 2020. The research sample in this study was direct processing data and factory overhead costs at Andra Bakery Medan in 2020. The data analysis technique in this study is a descriptive analysis method.Based on the results of the analysis and evaluation, it can be concluded that the cost of production per unit with the traditional method for banana bread is Rp. 1,090, for brown bread is Rp. 1,179, and for srikaya bread is Rp. 1,212. While the cost of production per unit using the activity based costing method, different results were obtained for banana bread of Rp. 1,084, for brown bread of Rp. 1,172, and srikaya bread of Rp. 1,229. This difference is caused because in the traditional method the overhead costs for each product are only charged to one cost driver, namely the number of production units. Meanwhile, in Activity Based Costing, overhead costs for each product are charged to 3 cost drivers, namely the number of production units, direct working hours, and area